Clinical aspects of growth hormone deficiency in adults : consequences of growth hormone deficiency and effects of replacement therapy : academisch proeschrift - Boer, Johannes Mathijs Maria de (ICG printing, 1995)
The publication focuses on growth hormone deficiency in adults and on hormone replacement therapy. Intended for professional public.
Keywords: dospělí; klinické lékařství; hormonální substituční terapie; Clinical Medicine; Human Growth Hormone; Hormone Replacement Therapy; endokrinologie; Adult; lidský růstový hormon